Molecular Detection of the Mutations in Khoderi Olive cultivar : NO - Al Rufaye, Ziena Thamer A.; Katham, Ayam Razak Abdal; Jawad, Hassan Jameel (Comunicata Scientiae, 2026)
The characterization of olive cultivars using molecular markers is necessary for genetic diversity conservation, cultivar verifiction, and the identification of locally adapted genotypes. This study searches for genetic variation in the Khoderi olive cultivar from Karbala, Iraq, utilization two genetic molecular regions: the nuclear ribosomal ITS1 spacer and the plastid matK gene. Through DNA was extracted using a modified CTAB protocol, amplified by PCR, and get sequenced utilization Sanger sequencing. Alignment and comparative analysis with reference sequences deposited in Gen-Bank the results revealed 92.3% similarity of the ITS1 sequence with the Khoderi-Bakraju cultivar with serial number (OQ134700.1), indicating genetic affinity but insufficient similarity for confirmed cultivar identity. The matK region showed 96% similarity with an Olea europaea subsp. europaea plastid genome with serial number (MG372119.1), we notice reflecting high conservation of the chloroplast coding sequences. Multiple SNPs and small indels were detected in both regions, representing intraspecific polymorphisms. The combined data suggest that the studied sample belongs to the broader O. europaea gene pool but may represent a distinct local genotype. Further analyses using high-resolution molecular markers (SSR, SNP-based GBS) are recommended to refine cultivar differentiation.